Magzā Surah Al-Naba’ [78] Perspektif Adi Hidayat: Analisis Tafsir Audiovisual di Youtube - Azzah Riscilia, Safira; Dewi Muharromah, Safira; Deva Ipe Febri Efendi, Schedtzi; Amru, Khobirul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
The Qur'an and al-Sunnah as guidelines for Muslims in carrying out all activities in the world are not only to obey the commands and stay away from Allah's prohibitions. But as a sign of life in the world is temporary and there will be life after death. The news of the afterlife was announced by Allah in the Qur'an in Surah al-Naba' [78]. With the passage of time, the method of da'wah has also developed. One of them is the form of da'wah through social media, which has become a new field for researchers, not least in the field of Al-Qur'an and interpretation. The author is interested in examining Adi Hidayat's perspective on revealing the news of the truth of life after death as one of the magzā surah al-Naba' [78] broadcast through Adi Hidayat's official YouTube account. In order to achieve this goal, this research uses a qualitative descriptive method with a content analysis approach. The results of this study are in the form of maghzā surah al-Naba' [78] from Adi Hidayat's perspective, which is the truth of the existence of life after death and Allah's answer to human beings the difference between those who disbelieve and those who believe. Adi Hidayat's ability to identify the meaning contained in the Qur'an makes it easier for listeners to understand and practice the Qur'an in their daily lives. Thus, human efforts to prepare as well as possible for the afterlife are the proof of the belief in the afterlife.